Coherence of European Union Actions at the UN Human Rights Council and the Council of Europe - Anatoly Boyashov (Vestnik MGIMO-Universiteta, 2019)
The current methodological debates on the EU external actions at international organisations raise the issue of the EU coherence. The scholarship tends to focus on EU vertical and horizontal coherence in various policies, making the EU internal coordination central in the analysis. Neither horizontal nor vertical EU coherence leads to understanding why the EU is accused of “double standards”. Little research explores the external contestation as a pivotal matter of the EU effectiveness, performance, actorness. It appears promising to make the EU action coherent over various multilateral bodies. This paper argues that the external environment is the key element for the external coherence of the EU action at the UN Human Rights Council (HRC) and the Council of Europe (CoE). It answers the research question: how to measure external coherence in EU action at the HRC/CoE? The proposed indicators are the following: 1) coherence in references to the UN/CoE and to the EU founding treaties and pivotal documents on human rights; 2) degree of external support/contestation for the EU objectives at the HRC/CoE; 3) degree of coherence of EU external representation to the HRC/CoE; 4) degree of coherence in formulating priorities and using instruments at the HRC/CoE. The paper provides the assessment by the UN, EU and non-EU experts of the EU external coherence, which is followed by policy recommendations.